Understanding the political economy of the Arab uprisings - Diwan, Ishac (World Scientific, 2014)
For the millions of citizens in the Arab World who came together in 2010-2011 to discover their common yearning for dignity and liberty, the real revolutions only began after the wave of protests. Understanding the Political Economy of the Arab Uprisings reassess the interests, potential and constraints of various socio-political players and their importance in the building of a constructive environment for democratic progress in the Middle East. Initiated by the Cairo-based Economic Research Forum and edited by Ishac Diwan, this invaluable volume features contributions by Middle East academics across the world. They examine the reasons behind the uprisings, how democratic transitions transpire, the role of Arab capitalism in the crises, and how the experiences of other countries such as Indonesia, Turkey and Iran, can forecast where these uprisings may lead the Middle East in the years to come. Contents: Preface; Introduction; The Genesis of the Uprisings: The Political Economy of Arab Presidents for Life and After (Roger Owen); Understanding Revolution in the Middle East: The Central Role of the Middle Class (Ishac Diwan); The Making of the Tunisian Revolution (Fadhel Kaboub); A Transition to Democracy?: On the Determinants of Democratic Transitions (Caroline Freund and Melise Jaud); Islamists in Power? Inclusion, Moderation, and the Arab Uprisings (Jillian Schwedler); Arab Capitalism in Crisis: Detecting Corruption and Evaluating Programs to Control It: Some Lessons for MENA (Jeffrey B Nugent); Enhancing Competition in a Post-Revolutionary Arab Context: Does the Turkish Experience Provide Any Lessons? (Izak Atiyas); Lessons from Elsewhere: Politico-Economic Developments in Turkey and The Transformation of Political Islam (1950-2010) (Hasan Ersel); Social Order, Rents, and Economic Development in Iran Since the Early 20th Century Hadi Esfahani; What Happened in the Early Years of Democracy: Indonesia's Experience (Akhmad Rizal Shidiq and Philips Jusario Vermonte). Readership: Graduate and research students, political scientists, economists, social scientists who specialize in the political economy of the Middle East and current affairs in the MENA Region.